Tari Marcok Sebagai Representasi Upacara Pengobatan Masyarakat Sungai Bungkal Kota Sungai Penuh: Kajian Bentuk Pertunjukan - Nabila Dwi Adianti; Erlinda Erlinda (Pusat Riset dan Inovasi Nasional, 2025)
Tari Marcok is a traditional performance that represents the healing ritual process of the community in Sungai Bungkal Subdistrict, Sungai Penuh City. However, many members of the community still do not fully understand the meanings behind the signs presented in this performance. This study generally aims to explore the presentation form of Tari Marcok and how it represents the values of the healing ritual embodied within it. A qualitative approach was employed, with the object of research being Tari Marcok created by Iskandar Zakaria. Data were obtained through direct observation, in-depth interviews, documentation, and literature studies. The theoretical frameworks used in this research include Ferdinand de Saussure’s semiotic theory to reveal the meaning of signs, Marcel Danesi’s concept of representation, and Sal Murgiyanto’s ideas to examine the role of dance within society. The findings show that Tari Marcok represents the values of the healing ritual through elements such as movement, properties, chants, and costumes—each rich with symbolism and spiritual meaning. Therefore, it can be concluded that Tari Marcok is not merely a performance, but a cultural representation of the traditional healing practices of the Sungai Bungkal community that continue to endure today.